2018
DOI: 10.1371/journal.pone.0203795
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative immune suppression is mediated via reversible, Interleukin-10 dependent pathways in circulating monocytes following major abdominal surgery

Abstract: IntroductionPost-operative infections occur frequently following major surgery. The magnitude of the post-operative immune response is associated with an increased risk of post-operative infections, although the mechanisms driving post-operative immune-dysfunction and the potential reversibility of this response with immune stimulants are not well understood. This study aims to describe the immediate immune response to major surgery and establish links to both post-operative infection and functional aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 50 publications
2
31
0
Order By: Relevance
“…These findings have been confirmed in multiple subsequent studies, which have suggested that both a more robust initial inflammatory reaction along with the inability to recover HLA-DR expression predispose and prognosticate trauma patients to subsequent development of sepsis [40, 41]. In addition, reduced HLA-DR expression has been observed within 24 h after surgery and can be restored through the application of granulocyte-macrophage colony stimulating factor (GM-CSF) and interferon-gamma (IFN-γ) [42]. Continued suppression of monocyte HLA-DR expression has also been correlated with a worse outcome in patients with sepsis [43].…”
Section: Mechanisms Of Post-injury Immune Dysfunctionmentioning
confidence: 97%
“…These findings have been confirmed in multiple subsequent studies, which have suggested that both a more robust initial inflammatory reaction along with the inability to recover HLA-DR expression predispose and prognosticate trauma patients to subsequent development of sepsis [40, 41]. In addition, reduced HLA-DR expression has been observed within 24 h after surgery and can be restored through the application of granulocyte-macrophage colony stimulating factor (GM-CSF) and interferon-gamma (IFN-γ) [42]. Continued suppression of monocyte HLA-DR expression has also been correlated with a worse outcome in patients with sepsis [43].…”
Section: Mechanisms Of Post-injury Immune Dysfunctionmentioning
confidence: 97%
“…Since every major surgical intervention results in stress for the patient's body and immune suppression during the postoperative recovery may occur, a patient undergoing elective surgery should to be as well prepared as possible, especially during the descend of the pandemic curve [101,102].…”
Section: Considerations On Perioperative Pharmacologic Prophylaxismentioning
confidence: 99%
“…Because perioperative inflammation always consists of a balance between a proand anti-inflammatory response, we measured IL-10 as an immunosuppressant cytokine and also detected a postoperative increase. Postoperative elevation of IL-10 has been well-described (24). The surgical impact also was associated with an increase in postoperative PTX3 and CRP after both surgeries.…”
Section: Discussionmentioning
confidence: 81%
“…As Tregs produce IL-10 (39) one could expect to see differences in the IL-10 response to the 2nd surgical procedure. However, Tregs are not necessarily the origin of postoperative systemically secreted IL-10, as it has been recently shown that a postoperative increase of IL-10 mRNA in patients' blood was not accompanied with FOXP3 mRNA increase but in fact a decrease (24).…”
Section: Discussionmentioning
confidence: 98%